Pengaruh Kualitas Produk,Citra Merek, dan Daya Tarik Iklan Terhadap Minat Beli Sepeda Motor Yamaha Alfa Scorpii Bengkong - Meri Christiani Tambunan; Hikmah Hikmah (SCIENTIA JOURNAL, 2026)
This study examines the influence of product quality, brand image, and advertising appealon purchase intention for Yamaha Fazzio motorcycles at Yamaha Alfa Scorpii BengkongBatam. The study was motivated by intense competition in the retro-modern scootersegment where Honda Scoopy still dominates market share compared to Yamaha Fazzio.The primary data was collected through questionnaires distributed to 172 respondents. Theresearch employed multiple regression analysis and multiple linear regression models todetermine the influence of independent variables (product quality, brand image, andadvertising appeal) on the dependent variable (purchase intention). The results indicatethat product quality, brand image, and advertising appeal simultaneously have asignificant influence on purchase intention for Yamaha Fazzio. The findings providevaluable insights for Yamaha Alfa Scorpii Bengkong's marketing strategy, emphasizing theimportance of improving product quality, strengthening brand image, and enhancingadvertising appeal to increase consumer purchase intention.